2012
DOI: 10.1155/2012/532576
|View full text |Cite
|
Sign up to set email alerts
|

Digital Heterodyne Holography Reveals the Non-Quasi-Static Scattering Behaviour of Transversally Coupled Nanodisk Pairs

Abstract: We reconstruct the full three-dimensional scattering pattern of longitudinal and transverse modes in pairs of coupled gold nanodisks using digital heterodyne holography. Near-field simulations prove that, in our experimental conditions, the induced dipoles in the longitudinal mode are in phase while they are nearly in opposite phase for the transverse mode. The scattering efficiency of the two modes is of the same order of magnitude, which goes against the common belief that antisymmetric transverse modes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…It is a consequence of larger electromagnetic coupling between the component particles for parallel than perpendicular light polarizations relative to the dimer axis. This effect, analog of the polarization dependence induced by the presence of a substrate (Section 3.1.3), has for instance been shown for single gold 103,170 and silver 211 homodimers (Fig. 19).…”
Section: Interacting Nano-objectssupporting
confidence: 57%
See 1 more Smart Citation
“…It is a consequence of larger electromagnetic coupling between the component particles for parallel than perpendicular light polarizations relative to the dimer axis. This effect, analog of the polarization dependence induced by the presence of a substrate (Section 3.1.3), has for instance been shown for single gold 103,170 and silver 211 homodimers (Fig. 19).…”
Section: Interacting Nano-objectssupporting
confidence: 57%
“…A very promising aspect of this method is that it yields access to the amplitude and phase of the field scattered by a nanoparticle and to the angular scattering pattern from a single hologram, using numerical reconstruction algorithms. [101][102][103] Using radially and azimuthally polarized laser beam excitation in a confocal microscope, detection and mapping of the 3D orientation of individual gold nanorods in a polymer film was recently achieved. Information was extracted through concomitant acquisition of photoluminescence signals and homodyne detection of the scattered field.…”
Section: Single-particle Linear Optical Techniquesmentioning
confidence: 99%
“…This included an upgrade of the conventional CCHM optical setup with a tunable laser and generalization of its theoretical framework toward arbitrary-distributed scatterers (see Methods for detailed description of CCHM and our experimental setup). The imaging of plasmonic nanoantennas by digital holographic microscopy was previously reported by Suck et al, who demonstrated the use of digital heterodyne holography for imaging of far-field maps produced by plasmonic nanoantennas. In their work, however, they focused only on measuring the intensity of the scattered field using the Kretschmann configuration and monochromatic illumination.…”
Section: Resultsmentioning
confidence: 84%